ZnO colloids and ZnO nanoparticles synthesized by pulsed laser ablation of zinc powders in water. (April 2020) - Chen, Wenguang; Yao, Chujun; Gan, Jie; Jiang, Kai; Hu, Zhigao; Lin, Jiamin; Xu, Ning; Sun, Jian; Wu, Jiada
Abstract: ZnO nanoparticles (NPs) were synthesized by pulsed laser ablation of zinc powders suspending in deionized water. The synthesized ZnO NPs were characterized for morphology, structure and optical properties. The ZnO NPs have irregular shapes sized in 10–50 nm and possess a wurtzite structure with polycrystallinity in nature, and grew without a preferential orientation. The supernatant solutions obtained by laser ablation of zinc powders in water exhibit the typical optical absorption edge of wurtzite ZnO near 380 nm and emit a photoluminescence composed of a narrow ultraviolet peak and a broad visible band, characteristics of the near-band-edge emission and the deep-level defects related emission of ZnO, respectively. The formation of ZnO NPs was further confirmed by structural and optical characterization performed for the aggregated ZnO NPs obtained by drop-casting the ZnO colloidal solutions onto Si wafers. And the effects of annealing in N2 on the structure and photoluminescence of the ZnO NPs transferred on Si were also examined.